1997
DOI: 10.1093/sleep/20.2.160
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Function in Mild Sleep-Disordered Breathing

Abstract: Although a broad range of neuropsychological deficits has been reported in patients with severe sleep disordered breathing (SDB), little is known about the impact of mild SDB on neuropsychological performance. In this study, we compared neuropsychological test performance in two groups of carefully screened volunteers who differed clearly according to the respiratory disturbance index (RDI). Controls (n = 20) were identified on the basis of an RDI < 5; cases (n = 32) had an RDI in the range of 10-30. Cases and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
3
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(129 citation statements)
references
References 0 publications
6
114
3
6
Order By: Relevance
“…Obstructive sleep apnea (OSA) is a highly prevalent disorder with serious cardiovascular [1][2][3][4][5][6][7][8] and neurocognitive consequences, 9 yet a considerable number of patients do not tolerate the most commonly prescribed treatment, continuous positive airway pressure (CPAP). [10][11][12][13][14][15] Therefore, novel approaches to OSA treatments are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) is a highly prevalent disorder with serious cardiovascular [1][2][3][4][5][6][7][8] and neurocognitive consequences, 9 yet a considerable number of patients do not tolerate the most commonly prescribed treatment, continuous positive airway pressure (CPAP). [10][11][12][13][14][15] Therefore, novel approaches to OSA treatments are needed.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25] Sleep disorders result in complaints about disturbed sleep, excessive daytime sleepiness, cognitive decline, and depression, all of which are also recognized as NMS of PD. [26][27][28][29] Additionally, sleep disorders have been shown to substantially impact healthrelated quality of life in patients with PD. 30 Few studies have assessed possible relationships between any given sleep disorder and different NMS in PD population.…”
mentioning
confidence: 99%
“…Both primary and secondary consequences of the obstructive respiration during sleep lead to emotional and behavioral alterations (1). Hypoxemia in the patients with OSAS may have different effects on the cognitive function and may lead to permanent anoxic damage to the central nervous system, neuronal lesions and atrophy in the hippocampus (9)(10)(11)(12)(13)(14)(15)(16)(17). For the patients with OSAS, it has been suggested that hypoxemia has negative regulating effect on the memory function and there is a significant reduction especially in short-term memory (1-3).…”
Section: Discussionmentioning
confidence: 99%